Shapers of Christian Orthodoxy : engaging with early and medieval theologians - Green, Bradley G., 1965- (Downers Grove, Ill. : IVP Academic, 2010)
"The purpose of this volume is threefold: to introduce a selection of key early and medieval theologians, to strengthen the faith of evangelical Christians by helping them to understand the riches of the church's theological reflection, and to help them learn how to think theologically"--From publisher description.
Irenaeus / W. Brian Shelton -- Tertullian / Gerald Bray -- Origen / Bryan Litfin -- Athanasius / Carl Beckwith -- The three Cappadocians / Robert Letham -- Augustine / Bradley G. Green -- Anselm / David Hogg -- Thomas Aquinas / Mark W. Elliott.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal -- History -- Early church, ca. 30-600.; Theology, Doctrinal -- History -- Middle Ages, 600-1500.; Theologians